Passive smoking and insomnia in rural Chinese nonsmoking housewives: An environmental and genetic perspective - Ming Jin; Huiting Chen; Jigen Na; Hang An; Zhiwen Li; Nan Li (Environment International, 2022)
Active smoking has been a risk factor for insomnia, however, little is known about the effect of passive smoking on insomnia. Polycyclic aromatic hydrocarbons (PAHs) are potential contents in tobacco smoke. We aimed to investigate the association between passive smoking exposure and insomnia, plus the modification effects of single nucleotide polymorphisms (SNPs) related to PAHs metabolism. A cross-sectional study with 392 nonsmoking women was conducted in a rural area of Shanxi Province, China. A structured questionnaire was used to collect the information on passive smoking exposure, insomnia and other health-related factors via face-to-face interviews. We simultaneously collected participants’ hair samples to measure the concentrations of 26 PAHs. Whole blood samples were collected to test 9 SNPs related to PAHs metabolism. Logistic regression analysis was conducted to evaluate the association between passive smoking and insomnia, as well as the relation between passive smoking and PAHs concentrations. We further examined the potential interaction effects between passive smoking and SNPs on insomnia. 118 (30.1 %) were exposed to passive smoking and 128 (32.7 %) suffered from insomnia. Passive smoking nearly doubled the probability of insomnia with adjusted odds ratio and 95 % confidence interval of (1.99: 1.16, 3.39). Dose-response association between passive smoking and insomnia was observed by passive smoking frequency (P trend < 0.001). Among the 7 PAHs measured with detection rates > 70 %, no specific PAH was detected to be associated with passive smoking exposure after Bonferroni correction. The mutant genotypes of CYP1B1 (rs1056836), AHR (rs2066853), and AHRR (rs2292596) were detected to have synergetic effects with passive smoking on insomnia after multivariate adjustment. We found a positive association between passive smoking status and insomnia among nonsmoking women. This association could be modified by SNPs related to PAHs metabolism. PAHs might not be the environmentally potential mechanism involved in the insomnia caused by tobacco smoke exposure.